Incidental Archaeologists : French Officers and the Rediscovery of Roman North Africa - Effros, Bonnie, 1965- (Book collections on Project MUSE., 2018)
"From 1830, the Roman ruins of North Africa intrigued invading French military officers and became key to the colonial narrative justifying French settlement of North Africa"--